Analisis penerapan prinsip syariah dalam produk pembiayaan Bank Syariah di Indonesia - Noviana, Velani Laily (Maliki Interdisciplinary Journal, 2026)
This study explores the implementation of sharia principles in Islamic banking financing products in Indonesia, focusing on murabaha, mudharabah, and musyarakah contracts. Islamic financial institutions are obliged to ensure that all financing activities remain free from riba, gharar, and maysir. The research employs a literature review approach, drawing on scholarly articles, regulatory frameworks issued by the Financial Services Authority (OJK), and standards of Islamic banking practice. Findings reveal that murabaha financing continues to dominate the financing portfolio due to its relatively low risk and strong alignment with market demand. In contrast, profit-sharing schemes such as mudharabah and musyarakah remain less prevalent, largely because of high monitoring costs and the potential for moral hazard. Overall, the application of sharia principles has been well established, yet further reinforcement of compliance mechanisms and innovation in contract design are necessary to enhance efficiency and strengthen the competitiveness of Islamic banks.